SOFT POWER MODEL TO STRENGTHEN HUMAN SECURITY AT THE TEMAJUK BORDER - Elyta Elyta (Sosiohumaniora, 2022)
The current state of Indonesia’s border areas is very worrying. This can be seen from the ongoing issues of illegal trade, smuggling, the dominance of the Ringgit currency, shifting of boundary markers, and the presence of illegal migrant workers. These things become indicators of the nationalism crisis in the country’s border areas, which is a study of human security. This study aims to implement a soft power model to strengthen human security at the Temajuk border. This study uses a mix-method by collecting qualitative and quantitative data. Qualitative is done by interview, observation, and literature study. While quantitative is done by distributing questionnaires that are carried out in the period from May 2021 to November 2021. The research subjects were 14 people of Temajuk Village. The study results found that the soft power model to strengthen human security at the Temajuk border, which has been analyzed, shows that there are stages to be passed. First, the investigation stage is carried out by investigating the potential for soft power at the Temajuk border. Second is the soft power model’s design and construction stage to strengthen human security at the Temajuk border. Third, the step of testing, evaluating, and revising the soft power model to enhance human security at the Temajuk Border consists of a pre-test and post-test. Implementing the soft power model in strengthening human security in the Temajuk border area is essential to effectively protect people who are vulnerable to human security threats.